SIRT7 deletion inhibits Glaesserella parasuis-mediated inflammatory responses in porcine alveolar macrophages - Zheng, Hao; Wang, Baoxin; Dong, Xia; Wu, Junjing; Shi, Liangyu; Zhang, Jing; Chen, Hongbo; Zhou, Ao (Frontiers in Cellular and Infection Microbiology, 2025)
Glaesserella parasuis (GPS) infection causes severe inflammatory disorder, resulting in lung injury. SIRT7 is an NAD+-dependent deacetylase known to regulate inflammatory responses, but its role in GPS infection remains unclear. Here we found that GPS infection increased SIRT7 expression and induced inflammatory responses. Deficiency of SIRT7 by CRISPR/Cas9 technology significantly inhibited GPS-induced cytopathic effects and inflammatory responses. In addition, RNA-seq analysis showed that differentially expressed genes(DEGs) induced by SIRT7 deficiency were enriched in biological processes such as cell proliferation, actin cytoskeleton formation, lipid synthesis, protein kinase activation regulation, and GTPase activity regulation. Functional enrichment analysis further indicated the involvement of these DEGs in tight junction pathway, PI3K-Akt signaling pathway, actin cytoskeleton regulation, cGMP-PKG signaling pathway, Hippo signaling pathway, and TNF signaling pathway. Finally, we identified some hub genes (GNAI3, GNAI1, JAK1, NDUFS8, CYC1) related to oxidative phosphorylation. In summary, our results demonstrate that SIRT7 is pivotal for GPS-induced inflammatory responses, which represents a promising target resistant to GPS infection.